Fundamental Approaches to Software Engineering: 21st International Conference, FASE 2018, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings - Alessandra Russo; Andy Schürr (Theoretical Computer Science and General Issues, 2018)
This book constitutes the proceedings of the 21st International Conference on Fundamental Approaches to Software Engineering, FASE 2018, which took place in Thessaloniki, Greece in April 2018, held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018.The 19 papers presented in this volume were carefully reviewed and selected from 63 submissions. The papers are organized in topical sections named: model-based software development; distributed program and system analysis; software design and verification; specification and program testing; family-based software development.